Application of a dynamo-based intelligent drawing review program in the general code for building fire protection - Case study of subsection 7.4.7 - Yong Xu; Min Liu; Taiyang Zhang; Hongyuan Tang; Yingda Zhang (Results in Engineering, 2025)
Manual architectural drawing reviews are often time-consuming, error-prone, and influenced by subjective factors. To address these issues, this paper presents a Dynamo-based intelligent review program integrated with Building Information Modeling (BIM), focusing on Subsection 7.4.7 of the General Code for Building Fire Protection. The program enables classification of evacuation components—exits, walkways, and stairs—and formulates visual review logic to automate the verification of total net evacuation widths. By inputting design prerequisites, the tool extracts BIM model data, performs compliance judgments, and outputs results in real-time. This approach improves review speed, accuracy, and standardization across diverse building projects. The case study demonstrates the practicality and scalability of the system in checking critical fire protection regulations. The proposed framework supports efficient design validation, reduces labor demands, and contributes to enhanced building safety. The method also lays a foundation for further development of comprehensive intelligent code-checking and automated design feedback systems in fire protection engineering.